Proceedings of the Twenty-Fourth Annual ACM-SIAM Symposium on Discrete Algorithms 2013
DOI: 10.1137/1.9781611973105.119
|View full text |Cite
|
Sign up to set email alerts
|

Morphing Planar Graph Drawings with a Polynomial Number of Steps

Abstract: In 1944, Cairns proved the following theorem: given any two straight-line planar drawings of a triangulation with the same outer face, there exists a morph (i.e., a continuous transformation) between the two drawings so that the drawing remains straight-line planar at all times. Cairns's original proof required exponentially many morphing steps. We prove that there is a morph that consists of O(n 2 ) steps, where each step is a linear morph that moves each vertex at constant speed along a straight line. Using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1
1

Relationship

5
2

Authors

Journals

citations
Cited by 21 publications
(58 citation statements)
references
References 23 publications
1
57
0
Order By: Relevance
“…(c) and (1), we conclude that for a large enough L 2 ⌦(L 0 + 0 ) we can guarantee the same two properties we needed in (1), that is, ↵ maps every small rectangle R e to a parallelogram ↵(R e ) whose diameter is at least 0 , and every nonhorizontal edge to a segment of length at least L 0 + 2 0 . Hence, every remaining contracted vertex v e in b D 0 can be split within the parallelogram ↵(R e ) as in (1).…”
Section: General Case By Inductionsupporting
confidence: 52%
See 2 more Smart Citations
“…(c) and (1), we conclude that for a large enough L 2 ⌦(L 0 + 0 ) we can guarantee the same two properties we needed in (1), that is, ↵ maps every small rectangle R e to a parallelogram ↵(R e ) whose diameter is at least 0 , and every nonhorizontal edge to a segment of length at least L 0 + 2 0 . Hence, every remaining contracted vertex v e in b D 0 can be split within the parallelogram ↵(R e ) as in (1).…”
Section: General Case By Inductionsupporting
confidence: 52%
“…Hence, every remaining contracted vertex v e in b D 0 can be split within the parallelogram ↵(R e ) as in (1). To finish the construction, it remains to apply the inductive hypothesis to fill in the missing parts in the maximal separating triangles or 4-cycles.…”
Section: General Case By Inductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two planar drawings, ψ 1 and ψ 2 , of G are isomorphic if there exists a continuous family of planar drawings {ψ (t) : 0 ≤ t ≤ 1} of G such that ψ (0) = ψ 1 and ψ (1) = ψ 2 . 2 We call a graph, G = (V , E) a geometric planar graph if it is the image of some planar drawing of a graph G = (V , E). That is, V (G) = {ψ(v) : v ∈ V (G)}, E(G) = {(ψ(u), ψ(w)) : (u, w) ∈ E(G)}, and ψ is a planar drawing of G. When clear from context, we will sometimes treat a geometric planar graph interchangeably with the set of points and line segments defined by its vertices and edges, respectively.…”
Section: Formal Problem Statement and Main Resultsmentioning
confidence: 99%
“…Since then, a sequence of results has shown that morphs can be done Figure 2: Computer-assisted animation frequently involves morphing between a sequence of drawings of the same planar graph. Zooming in on a section of the image reveals that the artist's strokes are approximated by polygonal paths efficiently, so that the motion can be described concisely [2,3,12,19]. The most recent such result [3] shows that any planar drawing of an n-vertex connected planar graph can be morphed into any isomorphic drawing using a sequence of O(n) linear morphs, in which vertices move along linear trajectories at constant speed.…”
Section: Introductionmentioning
confidence: 99%